2005
DOI: 10.1007/s11096-005-7113-8
|View full text |Cite
|
Sign up to set email alerts
|

Complex Pharmaceutical Care Intervention in Pulmonary Care

Abstract: Patients can be influenced effectively by the tailored intervention of pharmacists resulting in improved ability to cope with pulmonary medication and in fewer reported adverse effects and symptoms. Patients attributed these results to the intervention of the pharmacists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…after the delivery of intervention [39,40,42]. Most of the studies investigating satisfaction with cognitive services were randomised, 2 at patient level [48,49] and 2 at pharmacy level [45,46]. These cognitive service related studies either measured satisfaction pre and post service [46,47,49] or post-service only [45,48].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…after the delivery of intervention [39,40,42]. Most of the studies investigating satisfaction with cognitive services were randomised, 2 at patient level [48,49] and 2 at pharmacy level [45,46]. These cognitive service related studies either measured satisfaction pre and post service [46,47,49] or post-service only [45,48].…”
Section: Methodsmentioning
confidence: 99%
“…Administration modes ranged from self completion on site [42,44,47,51], provider/researcher administered either on site (face to face interviews) [28,32], or via telephone [40,41,46], or mailed [30,34,39,43,45,[47][48][49][50]. One innovative study reported the use of trained volunteer patients as 'mystery shoppers' to assess and report their satisfaction with services provided by different health care professionals [36].…”
Section: Methods Of Satisfaction Measurementmentioning
confidence: 99%
See 3 more Smart Citations